Differential crosstalk between global DNA methylation and metabolomics associated with cell type specific stress response by pristine and functionalized MWCNT. (January 2017) - Chatterjee, Nivedita; Yang, Jisu; Yoon, Dahye; Kim, Suhkmann; Joo, Sang-Woo; Choi, Jinhee
Abstract: The present study endeavored to evaluate the comprehensive mechanisms of MWCNT-induced toxicity with particular emphasis on understanding cell specificity in relation to surface functionalization of MWCNT. Following treatment with differentially functionalized (hydroxylation/carboxylation) MWCNT on human bronchial epithelial (BEAS-2B) and human hepatoma (HepG2) cell lines, intracellular uptake, various toxicological end points, global metabolomics profiling and DNA methylation were evaluated. Herein, the comparative in vitro studies ascertained that surface functionalization diminished the toxic potentiality of MWCNT in respect of their pristine counterpart. The surface enhanced Raman scattering with dark-field microscopy attested the intracellular uptake of functionalized-MWCNT, but not the pristine one. The MWCNT's exposure caused alterations in stress responses (oxidative stress, inflammation, profibrosis, DNA damage-repair), differential mode of gene expressions, global metabolomics and DNA methylation status (DNMT3B dependent hypo-methylation in BEAS-2B cells and hyper-methylation in HepG2 cells) in a cell type specific and surface functionalization dependent manner. The alterations in particular metabolites (choline, betaine, succinate etc.) and distinct DNA methylation crosstalk patterns are the possible underlying mechanisms of differential mode of gene expressions and cell type specificity of MWCNT. This study provides preliminary evidence of epigenetic modifications and global metabolomics profiling which might be translated for risk assessment of MWCNT.